KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA SALES PROMOTION GIRL (SPG) PENGGUNA SEPATU HAK TINGGI DI SUZUYA MEDAN PLAZA PADA TAHUN 2015 - nuansa putri; kalsum *; eka lestari mahyuni (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Sales promotion girl (SPG) that have risk of musculoskeletal disorders (MSDs) of limb muscles on the bottom of which are affected by the individual characteristics and the user of high heels for eight hours with minimum height of 5 cm when they are working. So, the research are done about complaining musculoskeletal disorders (MSDs) on Suzuya’s sales promotion girl at Medan Plaza in  2015. This research is descriptive with the sample as many as 64 people. Variable in the research are age, body mass index (BMI ), the duration of use shoes, and the height of heels. The results of research indicates based on age of respondents had a limb muscles on the bottom the largest is single age category  25-28 years with fourteen people (21,9 % ). Based on body mass index (BMI) respondents had a limb muscles, the highest is  in  the category of body mass index (BMI) with twenty people overweight (31,2% ). Based on the duration of use shoes of respondents had a limb muscles, the highest  is at the bottom of the shoes 2-6 years with twenty six people (40,6% ). And based on the height of heels of respondents who experienced complaints in the muscles the lower extremity most were into the category of a high shoes 7 cm as many as thirty seven people (57,8%). From the research suggested that sales promotion girl (SPG) do relaxation and stretch after 4  hours of work and to wear a sandal or flat shoes in rest time of work and going to home. the company suggested to assign a supervisor in the area to remind sales promotion girl (SPG) every a briefing time on the recommendations given by the author.